Faktor-faktor penentu keutamaan agihan zakat kepada asnaf oleh institusi zakat di Malaysia - Aryati Juliana, Sulaiman (2018)
Partial and disproportinate distribution of zakat among the eight asnaf and various distributions among zakat institutions in Malaysia caused the community to lose confidence and dissatisfied with the management of zakat institutions. This problem has inspired the researcher to conduct this study. This study aims to explain the form of zakat distribution, identify and determine the factors that influence the zakat distribution priority to asnaf made by zakat institutions. In achieving these objectives, a field study was carried out using structured questionnaires involving all the 14 zakat institutions which was represented by members of committee involved in zakat distribution. Using logistic regression analysis, this study found that two independent variables have significant relationship with the priority of zakat distribution to asnaf, namely economic status and political pressure. Economic status was found to have a significant relationship with the priority of zakat distribution to asnaf mualaf. This positive relationship is due to the concern of zakat institutions against the rising of apostasy cases. Political pressure also has a significant relationship with the priority of zakat distribution to asnaf amil but its relationship is negative. Zakat institutions are seen to be more careful in the distribution of zakat to asnaf amil so that they will not be accused of misusing zakat fund and free from political influence. Furthermore, political pressure was found to have a significant relationship with the priority of zakat distribution to asnaf al-gharimin. This positive relationship shows that the zakat institutions’ effort to co-operate with the government in dealing with debt problems among the people. Some management implications are suggested in this study to ensure the distribution of zakat to asnaf is made thoroughly and balanced. In summary, this study supports the theory of distribution justice and suggests that this theory to be extended in future studies.